The Fallacy of 'compartmentalisation': The West and Russia from Ukraine to Syria. Issue 1 (June 2016) - Cornell, Svante E.
In the post-Soviet space as well as the Middle East, Western leaders have largely failed to heed ample evidence that the goals of the Russian leadership are fundamentally opposed to those of the EU and the US. Whereas Moscow seeks to counter Western influence and roll back the US's role in the world, the West has proposed a win–win approach, seeking to convince Moscow that its 'true' interests should lead it to cooperate with the West. When this has not worked, Western leaders have 'compartmentalised', isolating areas of agreement from areas of disagreement. This approach has come to the end of the road because the assumptions that undergird it are false. So long as Western powers fail to understand the fundamental incompatibility of their interests with the deeply anti-Western interests of the current power brokers in the Kremlin, they are unlikely to develop policies that achieve success.